Two Level Factorial Design Using RSM For Screening Factors Of IPA Dehydration By Pervaporation Process Using PA Hollow Fibers - Wan Zulaisa Amira, Wan Jusoh; Sunarti, Abd Rahman; Abdul Latif, Ahmad; Nadzirah, Mohd Mokhtar (2017)
Purifiying the IPA from the aqueous solutions in the industry by PV is a well-established in the membrane separation technologies. PV has progressively become a prospective separation technique because of the benefits in term of energy efficiency, environment friendly and simple operation. To ensure an effective pervaporation process, the rela ted factors and their contributions need to be identified intensively. As one of the features in RSM, FFD were used to identify an approximating function for predicting future response for further analysis to determine fa ctor values that optimize the response function for lPA pervaporation. The factorial models have been obtained from experimental design to study all interactions among the considered parameters which were JPA concentration (70 – 95 wt %), feed temperature.(60 - 90°c), feet flow rate (30 – 100 L/hr) and permeate pressure{0.l - 5 kPa). The results; obtained from the analysis of vnriam e (ANOVA) of permeate flux and selectivity, showed that the iinpacts of JPA concentratjon and feed temperahtre are much more important than feed flow ra te and permeate pressure and the regression equa tion obtained to show the relationship between the responses.